KZ, Kampf, Kunst : Boris Lurie: NO!Art ; Katalog zur Ausstellung vom 27. August 2014 bis 2. November 2014 im Kölner NS-Dokumentationszentrum - Lurie, Boris 1924-2008; Satanovsky, Igor; Jung, Werner 1954-; NS-Dokumentationszentrum der Stadt Köln (NO!art Publ, 2014)
"The works of Boris Lurie have the power to shock. Many were created more than fifty years ago, but have lost none of their potential to rattle cages, to polarise opinion and to test the boundaries of tolerability. Boris Lurie's comprehensive and controversial works will be presented in the NS Documentation Centre in Cologne as of 27 August 2014. The exhibition -- developed in cooperation with the Boris Lurie Foundation in New York and under the curatorial direction of gallery owner Gertrude Stein -- features the first impressive works created directly after Lurie's release from Buchenwald concentration camp, as well as works from the 1940s and 1950s that have never been seen in Europe before. A selection of his impressive sculptural works from the 1970s will also be presented for the first time in the basement."--Gallery website